Case report: Unilateral panuveitis as a manifestation of Alport syndrome in a Chinese pediatric patient - Tian, Yu; Wu, Xiaochuan; Li, Yongzhen; He, Wenbin; Liu, Zibin; Myers, Frank L.; Zhou, Liang (Frontiers in Genetics, 2022)
Purpose: To report a rare case of a patient with Alport syndrome which was manifested as unilateral non-infectious uveitis after bilateral cataract surgery. Methods: A case report Results: A 2-year-old boy was diagnosed with unilateral uveitis based on the opacified vitreous and leakage of fluorescein angiography. Gene analysis and culture for the pathogen were negative. However, urine tests found blood cells and kidney pathology revealed a thickened membrane. A diagnosis of Alport syndrome was made. The patient was treated with oral steroids. The uveitis resolved gradually. Conclusion: Uveitis may be an ocular manifestation of Alport syndrome. Keywords: Alport syndrome, uveitis, COL4A5, pediatric, collagen